Correction: Collective motion of chiral Brownian particles controlled by a circularly-polarized laser beam. Issue 11 (11th March 2021) - Hernández, Raúl Josué; Sevilla, Francisco J.; Mazzulla, Alfredo; Pagliusi, Pasquale; Pellizzi, Nicola; Cipparrone, Gabriella
Abstract : Correction for 'Collective motion of chiral Brownian particles controlled by a circularly-polarized laser beam' by Raúl Josué Hernández et al., Soft Matter, 2020, 16, 7704–7714, DOI: ; 10.1039/C9SM02404B .